Potensi Aktivitas Ekstrak Etanol Daun Pucuk Merah (Syzygium myrtifolium Walp.) sebagai Antihiperurisemia pada Mencit Putih (Mus musculus) - Lusi Indriani; Ayu Rahmawati; Nursyafni; Nawwar Irfan; Novita Sari (The Journal Of Pharmacy, 2023)
Hyperuricemia is a condition where uric acid production increases or the kidneys cannot remove uric acid from the body so that uric acid levels in the blood exceed 7.0 mg/dL in men and 6.0 mg/dL in women. One of the secondary metabolites that have the potential to act as anti-hyperuricemia is flavonoids. Red shoots contain flavonoids, alkaloids, terpenoids, chalcones, and tannins. This study aimed to determine the anti-hyperuricemia activity of ethanol extract of red shoots (Syzygium myrtifolium Walp.) in white mice. This study used 16 male white mice which were randomly divided into 4 treatment groups. Group 1 was negative control (Na-CMC 0.5%), group 2 was positive control (allopurinol 300 mg/KgBW), group 3 was dose 1 (pucuk merah ethanol extract 10 mg/kgBW), and group 4 was dose 2 (pucuk merah ethanol extract 15 mg/KgBW). Before giving treatment, mice were first induced with KBrO3 at a dose of 148 mg/KgBW intraperitoneally and initial uric acid levels were measured. Then each group was given oral treatment. Uric acid levels were measured at 30, 60, and 90 minutes. The results showed that the pucuk merah ethanol extract 15 mg/KgBW (dose 2) had an anti-hyperuricemia activity of 62.42% compared to allopurinol 65.80%.